Dye-doped cholesteric lasers: Distributed feedback and photonic bandgap lasing models. (May 2015) - Ilchishin, Igor P.; Tikhonov, Eugene A.
Abstract: A review of authors' contributions to dye-doped cholesteric liquid crystal (CLC) lasers started from the pioneer authors' paper of 1980 in which the experimental realization of the first CLC laser is presented. Both distributed feedback (DFB) and photonics band edge lasing models are discussed for different experimental conditions. A detailed study and analysis of basic characteristics of steroidal CLC lasers with low liquid crystal optical birefringence is considered with respect to the DFB model. The manifestation of a planar texture quality and mutual orientations of directors on the substrates influencing on the lasing characteristics in steroidal CLCs have been shown and described. The reversible phototuning of the CLC laser wavelength by trans–cis transitions of photoactive components is realized. Reasons for two theoretical models׳ coexistence for the description of dye-doped CLC lasing is considered. Highlights: Lasing in steroidal CLC is related to the DFB model at high gain and its modulation. Spatial structure of CLC-laser beam can be described by the Laguerre–Gauss modes. Lasing efficiency of CLC also depends on the induced thermal diffraction grating. Oriented textures of CLC are stable for powerful single pulse pumping up to 100 ns.